Iron Biofortification of the Common Bean: Assessment of Bean Iron Concentration and Iron Bioavailability from Markets and Breeder Collections in East Africa. (29th May 2020) - Glahn, Raymond; Wiesinger, Jason; Lung'aho, Mercy
Abstract: Objectives: To assess the practicality and assumptions of the high Fe concentration approach for bean Fe biofortification in east Africa. Methods: A collection of 76 marketplace samples (East Africa Marketplace Collection; EAMC) were assembled, consisting of multiple color classes from locations in Uganda, Rwanda, Democratic Republic of Congo, Burundi, Ethiopia, Kenya and Tanzania. In addition, because market samples can be a mixture of seed varieties within a market class, 170 samples from the Africa CIAT Collection were also assembled that represent beans of common markets in the region. Iron concentration was measured via inductively coupled plasma emission spectroscopy (ICP-ES) and Fe bioavailability via an established Caco-2 cell bioassay. Using these measures, the following assumptions of high Fe bean Fe biofortification approach were assessed: 1) the average Fe concentration in beans currently consumed in east Africa is approximately 50 μg/g (dry weight), 2) a 40 μg/g increase (target value 90 μg/g) can be sustained through traditional breeding, and 3) iron bioavailability from the biofortified bean will not decrease substantially to negate the increase in Fe concentration. Results: The average EAMC bean Fe concentration was 72 μg/g, ranging from 52–93 μg/g, with a couple of outlying varieties at 105 μg/g (MAC9) and 129 μg/g (MAC49). The Africa CIAT collection averaged 67.5 μg/g with a range of 51–90 μg/g. The 18 biofortified varieties within the EAMC averaged 73 μg/g (range of 55–94 μg/g), which is essentially equal to the overall mean (70 μg/g) and range (54–93 μg/g) of the non-biofortified bean varieties in the EAMC. Using a Caco-2 cell bioassay to measure Fe bioavailability of the EAMC, the biofortified varieties did not deliver any additional Fe relative to non-biofortified varieties. Conclusions: The results indicate that the assumptions of the high Fe bean breeding approach are not met in the typical east African market place. Furthermore, based on the Fe content and bioavailability data collected from this study, the biofortified bean varieties from these markets are providing no additional dietary Fe. An alternative approach for bean Fe biofortification, such as enhanced Fe bioavailability should be pursued. Funding Sources: USDA.